Social Media and the Journalist–Source Relationship: How Digital Death Knocks Might Exacerbate Moral Injury - Alysson Lee Watson (Journalism and Media)
Social media use is commonplace for journalists in newsgathering, including reporting newsworthy deaths. Journalists have revised their death knock practice of physically doorknocking bereaved families to a preference for digital methods to solicit comment and context for stories about fatal incidents. This is gleaned from social media. A 2021–2022 Australian mixed-methods study, including a survey and semi-structured interviews, found that journalists use social media as a tool to find, contact, and interview people, and as a source of facts, photographs, and comments for stories. Journalists are at risk of moral injury, which occurs when they breach their own moral code, including through institutional betrayal. This article argues the digital death knock increases the risk of moral injury because unfettered access to, and sanctioned use of, social media material creates new ethical complexities. It proposes that fundamental to the journalist’s risk of moral injury is their view of the journalist–source relationship, which might in turn reflect their underlying ethical framework. The journalist who preferences utilitarian ethics—the greatest good for the greatest number—may see a source as means to an end; however, the journalist who preferences deontological ethics—respect for persons as an end in themselves—may owe the source a greater duty of care, which, if breached, may make them vulnerable to moral injury.